Influence of the Acceptor Fluid on the Bupivacaine Release from the Prospective Intra-Articular Methylcellulose Hydrogel - Dorota Wójcik-Pastuszka; Anna Frąk; Witold Musiał (Pharmaceutics, 2024)
Injections are one way of delivering drugs directly to the joint capsule. Employing this possibility, local anesthetic, such as bupivacaine (Bu), in the form of the suspension can be administered. The aim of this work was to propose a methylcellulose-based hydrogel-incorporated bupivacaine for intra-articular injections and to study the release kinetics of the drug from the hydrogel to different acceptor media, reflecting the synovial fluid of a healthy joint and the synovial fluid of an inflamed joint. The drug release studies were performed employing the flow apparatus. The drug was released to four different acceptor fluids: phosphate buffer pH = 7.4 (PBS7.4), phosphate buffer pH = 6.8 (PBS6.8), phosphate buffer pH = 7.4 with the high-molecular-weight sodium hyaluronate (PBS7.4H), and phosphate buffer pH = 6.8 with the low-molecular-weight sodium hyaluronate (PBS6.8L). The investigation was carried out at the temperature of 37 °C. The absorbance of the Bu released was measured at the wavelength of 262 nm every 2 min for 24 h. The release profiles of Bu to the acceptor media PBS7.4, PBS6.8, PBS7.4H, and PBS6.8L were described best by the first-order kinetics and the second-order equation. According to these models, the release rate constants were the highest when Bu was released to the fluid PBS7.4 and were k1 = (7.20 ± 0.01) × 10−5 min−1 and k2 = (3.00 ± 0.04) × 10−6 mg−1 × min−1, respectively. The relative viscosity of the acceptor medium, its pH, and the addition of high-molecular-weight or low-molecular-weight sodium hyaluronate (HAH or HAL) to the acceptor fluid influenced the drug dissolution. The release of Bu into the medium reflecting healthy synovial fluid takes a different pattern from its release into the fluid of an inflamed joint.